2019
DOI: 10.1002/hpja.244
|View full text |Cite
|
Sign up to set email alerts
|

Association of the LiveLighter mass media campaign with consumption of sugar‐sweetened beverages: Cohort study

Abstract: Issue addressed Evaluation of the behavioural impact of Western Australia's LiveLighter healthy weight and lifestyle campaign focussed on decreasing consumption of sugar‐sweetened beverages (SSBs) using graphic imagery, as well as monitoring unintended consequences. Methods A cohort design with pre‐campaign telephone survey of Western Australian adults aged 25‐49 (Time 1 May/Jun 2013: N = 1504) undertaken and repeated following the campaign (Time 2 Aug/Sep 2013: N = 822). Results Post‐campaign awareness was 67… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…This study extends the literature on the important role of media campaigns in addressing behavioral risk factors [30][31][32][33][34]. It replicates findings from high-income countries, and as in other public health applications, it shows that media campaigns for obesity prevention can play a crucial role in improving awareness, and changing knowledge, attitudes, and social conversations around obesity and its behavioral risk factors [30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study extends the literature on the important role of media campaigns in addressing behavioral risk factors [30][31][32][33][34]. It replicates findings from high-income countries, and as in other public health applications, it shows that media campaigns for obesity prevention can play a crucial role in improving awareness, and changing knowledge, attitudes, and social conversations around obesity and its behavioral risk factors [30][31][32][33][34].…”
Section: Discussionsupporting
confidence: 82%
“…A significant body of evidence has found mass media campaigns to play a critical role in advancing public health. Traditionally, media campaigns have been used to promote social and behavioral change, from the prevention and control of infectious diseases to family planning to, more recently, addressing noncommunicable diseases [ 30 , 31 , 32 , 33 , 34 ]. In the context of obesity prevention, media campaigns have successfully improved knowledge, personal relevance, or concern over obesity [ 35 , 36 , 37 , 38 ], and there is some evidence, although more limited, for the effectiveness of media campaigns in improving behavioral intentions and actions [ 38 , 39 , 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, those with higher education were more likely to report seeing healthy eating campaigns than those with lower education levels in all countries except Canada, as were males compared with females in Canada, Mexico and the USA. Previous studies examining healthy eating campaigns have shown mixed results with regard to socio-demographic differences: some reported no differences in campaign awareness by sex, BMI or SES (22,24) , whereas others have found higher awareness among higher socio-economic groups (29,41) , and differences in campaign awareness by ethnicity (41) , sex and/or age (23,25,29,41) . Similarly, a review examining differences in the impact of physical activity campaigns by SES found mixed results with regard to differences by SES (72) .…”
Section: Discussionmentioning
confidence: 96%
“…A later study found higher post-campaign awareness (67 %), including high viewership among respondents residing in areas of low socio-economic status (SES). It also found increased knowledge of the health risks of sugarsweetened beverage (SSB) consumption, decreased SSB consumption among frequent SSB consumers as well as overweight SSB consumers, and an overall reduction in sugary food intake (23) . Another study examined the LiveLighter ® Sugary Drinks campaign, which centred around the visceral 'toxic fat' that accumulates around organs and leads to negative health consequences.…”
Section: Australiamentioning
confidence: 99%
“…In Australia, the evaluation of the LiveLighter mass media campaign targeting sugary drinks indicates a high campaign recall and modest reductions in SSBs [ 4 , 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%